Paths to long‐term performance and strategic planning1. (25th April 2019) - Shin, Sang Yoon
Abstract: A firm may ensure sustainability by pursuing long‐term performance through one of the three possible paths: adoption of long‐term perspectives within the existing business, extension into a new business and adoption of long‐term perspectives, and jump into the long‐term new business. Considering temporal dimension and business dimension, a firm pursues four types of performance: maintenance, sustainable growth, diversification, and transformation. Explorative strategic planning as well as exploitative one is required for a firm to successfully manage a balanced pursuit between long‐term performance and short‐term one.